Personality and unemployment - Frisancho Vera, Dora (1998)
It is applied the Rorschach to a group of bidden farewell and to other of workers in exercise of the Municipality of Lima, Peru. The differences impact in answers increase little detail and acromatic color so decrease of popular answers, that underline a restriction of the perceptual field and of the common sense in the bidden farewell.